Lew Wallace papers - Wallace, Lew, 1827-1905.
ALS (1864 September 2) written by Wallace to Benson John Lossing and photocopies of a letter (undated) from Wallace to John Page Nicholson, maps of the Battle of Shiloh attributed to Don Carlos Buell and Ulysses S. Grant, and sketch of Wallace's line of march at Shiloh.
In part, negative photocopies.
Lawyer, author, army officer, and diplomat. Full name: Lewis Wallace.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Buell, Don Carlos, -- 1818-1898.; Grant, Ulysses S. -- 1822-1885.; Lossing, Benson John, -- 1813-1891 -- Correspondence; Nicholson, John P. -- 1842- -- Correspondence; United States. -- Army -- History -- Civil War, 1861-1865.; Shiloh, Battle of, Tenn., 1862.; Tennessee -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Maps; Army officers; Authors; Diplomats; Lawyers